2016
DOI: 10.1038/srep29608
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid-contaminated pollinator strips adjacent to cropland reduce honey bee nutritional status

Abstract: Worldwide pollinator declines are attributed to a number of factors, including pesticide exposures. Neonicotinoid insecticides specifically have been detected in surface waters, non-target vegetation, and bee products, but the risks posed by environmental exposures are still not well understood. Pollinator strips were tested for clothianidin contamination in plant tissues, and the risks to honey bees assessed. An enzyme-linked immunosorbent assay (ELISA) quantified clothianidin in leaf, nectar, honey, and bee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 50 publications
6
91
1
2
Order By: Relevance
“…Mogren and Lundgren (2016) assessed neonicotinoid concentrations in the nectar of five wild flower species sown as part of pollinator conservation measures which were located adjacent to neonicotinoid-treated maize. This was achieved by collecting honeybees seen to visit these flowers for nectar and extracting the contents of their crop for neonicotinoid residue analysis.…”
Section: Evidence For Exposure To Neonicotinoid Pesticidesmentioning
confidence: 99%
“…Mogren and Lundgren (2016) assessed neonicotinoid concentrations in the nectar of five wild flower species sown as part of pollinator conservation measures which were located adjacent to neonicotinoid-treated maize. This was achieved by collecting honeybees seen to visit these flowers for nectar and extracting the contents of their crop for neonicotinoid residue analysis.…”
Section: Evidence For Exposure To Neonicotinoid Pesticidesmentioning
confidence: 99%
“…The data confirms that nectar concentrations of some neonicotinoids were low in this study, likely due, in part, to the small quantities of nectar available for analysis. Previous studies have found that concentrations of neonicotinoids in nectar are often (but not always) lower than those found in pollen Mogren & Lundgren 2016).…”
Section: Pesticides Residue In Pollen and Nectarmentioning
confidence: 99%
“…Growing evidence for their toxic impacts on bee populations range from reduced queen production [73], disorientation [76], reduced immunity [77], and mortality [76,78]. Though much of the research on the effect of neonics has focused on honeybees, evidence has also shown that such pesticides are also harmful to wild bee populations [79].…”
Section: Searching For a Smoking Gun For Pollinator Declinesmentioning
confidence: 99%